Quality-Focused Design of Medical IoT Quality Management Systems - Han, Shihui (Auckland University of Technology, 2021)
Risk management of medical equipment before it is put into service is essential to reduce the risk of medical devices failing. Manufacturers of medical devices are required to minimize the risks associated with the use of medical devices. As medical devices are a mission critical product, any degree of error can result in patient death or health compromise. The purpose of this study is to develop a quality management system based on medical device standards to help medical device manufacturers more effectively reduce the risk of medical device use and provide 100% reliable medical products. A system literature review (SLR) was implemented to demonstrate the connection between medical device standards (ISO 13485, ISO 14971, IEC 62366 and IEC 62304) and software architecture documents (ISO 25010 and 4+1 Views Model) as well as the relationship between recent reference medical device software architectures and software architecture documents. The main objective of the SLR is to comply with the requirements of the medical device standard in order to reduce the risk of medical device use and to select the best medical device related architecture that supports the architecture documents. ISO 14971 is the standard related to risk management for medical devices. In this study, we used the risk management process from ISO 14971 and selected three quality attributes from ISO 25010 including, learnability, user error protection and modifiability to design the software architecture and develop a quality management system. The second outcome of this research is to develop a Risk Management system to help medical device manufacturers reduce the risk of using medical devices. The process of risk management was based on the risk management process in ISO 14971.
Keywords: QMS; Medical IoT; Software Architecture; Medical Standard